Strengthening Indonesia’s National Police Directorate for Enhanced Protection of Women and Children - Wirayati, Ayu Nurasyifa; Retno, Nola; Fikri, Ahmad Ma'mun (LifeSciFi, 2025)
Crimes against the protection of women and children (Tindak Pidana Perdagangan Anak/TPPA) and human trafficking offences (Tindak Pidana Perdagangan Orang/TPPO) are serious transnational crimes that violate human rights and threaten social order. In Indonesia, TPPA and TPPO cases rose significantly from 2023 to 2024, exposing a persistent gap between legal frameworks and their practical enforcement. This study analyzes the evolution of TPPA and TPPO case handling by reviewing relevant regulations, examining annual case data, and identifying key challenges in the prevention and prosecution of these cases. Adopting a qualitative descriptive approach, this study draws on statistics from the Ministry of Women’s Empowerment and Child Protection and the Indonesian National Police, supplemented by a review of relevant legislation. Findings indicate that while reported cases continue to increase, resolution rates remain low due to the limited availability of specialized personnel, inadequate infrastructure, particularly in remote regions, weak inter-agency coordination, low public awareness, and insufficient victim protection. A notable legal development in 2024 is the creation of a dedicated TPPA and TPPO Directorate within the National Police, aimed at improving investigative procedures, institutional structures, and human resource capacity. The study concludes that stronger regulatory implementation, improved coordination, and comprehensive victim support are essential to address the ongoing enforcement gap.